2006
DOI: 10.1590/s1415-47572006000100032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone on fatty acid synthase gene expression in porcine adipose tissue cultures

Abstract: We describe an efficient in vitro assay to test growth hormone effects on mRNA levels and fatty acid synthase (FAS, EC. 2.3.1.85) activity. Swine adipose tissue explants were long-term cultured in medium containing growth hormone and FAS mRNA levels and enzyme activity were measured. We quantified FAS transcripts by competitive reverse transcriptase PCR (RT-PCR) using total RNA from cultured adipose tissue explants and RT-PCR standard-curves were constructed using a cloned 307 bp segment of native FAS cDNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…In contrast, Choi et al (2000) observed no alterations in FAS mRNA expression when immature 3T3-L1 adipocytes were cultured with trans-10, cis-12 CLA. In a previous study, where the effects of pGH were evaluated under the same conditions, José et al (2006) observed a reduction of 22% in FAS enzymatic activity, which was accompanied by 70% of reduction in mRNA abundance after 48 h of incubation. In the present study, the effects were similar in direction, but of different magnitude.…”
Section: Effect Of Trans-10 Cis-12 Cla On Lipid Metabolism Results Amentioning
confidence: 79%
“…In contrast, Choi et al (2000) observed no alterations in FAS mRNA expression when immature 3T3-L1 adipocytes were cultured with trans-10, cis-12 CLA. In a previous study, where the effects of pGH were evaluated under the same conditions, José et al (2006) observed a reduction of 22% in FAS enzymatic activity, which was accompanied by 70% of reduction in mRNA abundance after 48 h of incubation. In the present study, the effects were similar in direction, but of different magnitude.…”
Section: Effect Of Trans-10 Cis-12 Cla On Lipid Metabolism Results Amentioning
confidence: 79%
“…In growing swine, 80% of fatty acid is a result of de novo synthesis, using glucose as substrate, because only a low proportion of calories in their normal feed is present as fatty acids, and about 40% body glucose usage is destined for fat deposition in adipose tissue (José et al, 2006). The addition of glycerin reduced corn inclusion in the experimental diets and, therefore, lower the substrate for synthesis and transport of fatty acids by the liver, suggesting a reduction of circulating cholesterol and triglycerides.…”
Section: Serum Biochemical Indicatorsmentioning
confidence: 99%
“…Reduction in FASN expression in adipose tissue and liver leads to increased lipid oxidation (211,212). Increased FASN expression in adipose tissue increases lipogenesis (213).…”
Section: 5! Discussionmentioning
confidence: 99%